“Ukrainian Magazine” as source of history of Ukrainian journalism (from fonds of Department of Ancient and Rare Books of Institute of Book Studies of V. I. Vernadskyi National Library of Ukraine) - Loshchynska Nataliia (Рукописна та книжкова спадщина України)

(untitled)
The goal of the research of the article is to trace, using the example of the “Ukrainian Magazine”, the main regularities in the process of the birth of Ukrainian journalism in the conditions of the dominance of Russian imperial culture. Methodology. The research uses general scientific methods of cognition: inductive, analytical, comparative, generalization of information, historical-narrative method. Thanks to their comprehensive application, it became possible to more thoroughly investigate journal publications of various nature and give them anobjective assessment. Scientific novelty consists in the detailed study of the prerequisites for the publication under study, the activities of the editorial board, which contributed to the identification of its positive features and shortcomings. Conclusions. The collections of the V.I. Vernadskyi National Library of Ukraine contain many periodicals of the 19th century. The largest thematic group consists of magazines of universal content. The proposed articlegives an idea of the birth of the Ukrainian periodical in the territory of the Slobozhanshchyna region, its close connection with the higher educational institutions of that time through the prism of the multifaceted publications of the “Ukrainian Magazine”, which will be 200 years old in 2024. Attention is paid to establishing the classification of articles by thematic direction. On the basis of the then and modern scientific explorations, bibliographic indexes, memoir materials, letters, etc., the author found out the role of the “Ukrainian Magazine” in the social, public-political and cultural-artistic life of Ukraine, its significance for the development of the culture of the Kharkiv Region and Ukraine in general. It was emphasized that for most readers, the magazine was the only way to get acquainted with the achievements of foreign cultures, achievements in some fields of science, views on the political situation in the country and the world. The conclusion is made about the undeniably important role of the magazine in the literary process of the 20s of the 19th century.